(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background:Violence against female is an important and serious public health and medico-legal problem. It carries important risk factor related to ill health of female and its consequences on physical, social, mental and reproductive health of women. Objectives:To determine the type of fatal and non-fatal intentional injuries involving women, girls and young female kids and method used for such injuries and to reveal the magnitude of domestic violence of both physical and sexual types. Methods: A cross-sectional study was carried out within 6 months period on 82 medico-legal female cases with intentional violence. All females (living and postmortem cases) were studied. Information was collected from the same victim or her relative (in non-living cases) through an interview, police reports and their medical reports. Digital photography was done for some interesting cases while radiological survey followed by complete autopsy for all non-living cases. Results:The study showed that 57.3% were living subjects while 42.7% were postmortem victims. Regarding the living cases, their mean age was 20.61±9.37 years. Illiteracy constitutes 57.4% of them. All of them were referred as cases of violence directed to the genital area (sexual assault) but 72.3% were with no tear to the hymen. In post-mortem victims, the mean age was 28.6±12.84years. Housewives constituted 85.7% of them and 45.7% were having primary school level of education only. Burn was the main type of injury constituting 71.4%. In 65.71% were affected by sexual assault and in 69% of victims there were old hymen tears. In 80% death was due to suicide. Conclusion:Violence was more common among living female and highest in the third decade of life. Majority were either with low level of education or having primary school level of education. All of the living females were sexually assaulted while burn was the main type of injury among the postmortem group. Key words:Violence, Hymen, women, female.